Reducing the Meta-Emotional Problem Decreases Physiological Fear Response during Exposure in Phobics - Couyoumdjian, Alessandro; Ottaviani, Cristina; Petrocchi, Nicola; Trincas, Roberta; Tenore, Katia; Buonanno, Carlo; Mancini, Francesco (Frontiers in Psychology, 2016)
Anxiety disorders may not only be characterized by specific symptomatology (e.g., tachycardia) in response to the fearful stimulus (primary problem or first-level emotion) but also by the tendency to negatively evaluate oneself for having those symptoms (secondary problem or negative meta-emotion). An exploratory study was conducted driven by the hypothesis that reducing the secondary or meta-emotional problem would also diminish the fear response to the phobic stimulus. Thirty-three phobic participants were exposed to the phobic target before and after undergoing a psychotherapeutic intervention addressed to reduce the meta-emotional problem or a control condition. The electrocardiogram was continuously recorded to derive heart rate (HR) and variability (HRV) measures and affect ratings were obtained. Addressing the meta-emotional problem had the effect of reducing the physiological but not the subjective symptoms of anxiety after phobic exposure. Present preliminary findings support the role of the meta-emotional problem in the maintenance of the response to the fearful stimulus (primary problem).